2014
DOI: 10.1007/s10072-014-1752-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of frovatriptan and other triptans in the treatment of acute migraine of normal weight and obese subjects: a review of randomized studies

Abstract: An association between obesity and migraine has been observed in recent studies and it is supported by plausible biological mechanisms. The objective of this study is to evaluate the efficacy of frovatriptan and other triptans in the acute treatment of migraine, in patients enrolled in three randomized, double-blind, crossover, Italian studies and classified according to body mass index (BMI) levels, as normal weight or non-obese (NO, BMI 18.5-24.9 kg/m(2)) and overweight or obese subjects (O, BMI ≥ 25 kg/m(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…High BMI has been associated with severe and progressive forms of migraine in previous studies and may reflect a pro‐inflammatory state in obesity that renders treatment less effective. Inadequate 2hPF rates have been demonstrated in obese participants compared with normal‐weight subjects for triptans . Among headache characteristics, average headache pain intensity and the presence of cutaneous allodynia were associated with inadequate response at 2 hours, but monthly headache day frequency was not.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…High BMI has been associated with severe and progressive forms of migraine in previous studies and may reflect a pro‐inflammatory state in obesity that renders treatment less effective. Inadequate 2hPF rates have been demonstrated in obese participants compared with normal‐weight subjects for triptans . Among headache characteristics, average headache pain intensity and the presence of cutaneous allodynia were associated with inadequate response at 2 hours, but monthly headache day frequency was not.…”
Section: Discussionmentioning
confidence: 96%
“…Inadequate 2hPF rates have been demonstrated in obese participants compared with normal-weight subjects for triptans. 20 Among headache characteristics, average headache pain intensity and the presence of cutaneous allodynia were associated with inadequate response at 2 hours, but monthly headache day frequency was not. Prior studies suggest that baseline pain intensity and cutaneous allodynia predict a poor response to acute treatment.…”
Section: Discussionmentioning
confidence: 98%
“…182 Similarly, frovatriptan, in contrast to other triptans, retained a sustained antimigraine effect on obese subjects, possibly because of its longer half-life. 183 Chronic pain pharmacotherapy should address the concerns of obese patients about iatrogenic weight gain associated with some commonly used pain medications, such as gabapentin or pregabalin. One study showed that about 80% of patients taking 150 to 600 mg/d pregabalin for 1 year maintained their weight within 7% of baseline, but the remainder experienced more than 7% weight gain, and no one had weight loss.…”
Section: Pharmacotherapy For Pain In Obese Patientsmentioning
confidence: 99%
“…In drug clinical trials, the choice of the frequency of headache used to de ne episodic migraine in trials of new drugs has always been a di cult problem. Some clinical trials chose a headache frequency from 3 to 8 days per month (23), some chose from 1 to 6 days per month (24), and some chose from 2 to 8 days per month (25). However, there is no relevant clinical research indicating the number of days that should be selected as the standard, the number of days that would be appropriate to select based on the study design, and the number of days that is the most common frequency among patients in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%